1992
DOI: 10.1902/jop.1992.63.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Serial Doxycycline and Metronidazole in Prevention of Recurrent Periodontitis in High‐Risk Patients

Abstract: The efficacy of metronidazole and doxycycline in preventing recurrent periodontitis was studied in 23 patients. After treatment in the previous 7 months with either bimonthly scaling and 3 weeks of systemic doxycycline (11 subjects) or scaling and placebo (12 subjects), patients were monitored for recurrent periodontitis and were scaled every 2 months. When either a periodontal abscess or greater than 2 mm loss of gingival attachment was observed, metronidazole was administered (250 mg every 8 hours) for 10 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…As people ages, the ability of host defense mechanism may decrease with increase in the influence of accumulated periodontal destruction resulting in gradual tooth loss. Another epidemiologic study also suggested that specific bacteria played an important role in older adults with periodontal disease 26. In both univariate and multivariate logistic regression analysis of this study, old age groups showed significantly higher odds ratios and higher tooth loss rate.…”
Section: Discussionsupporting
confidence: 60%
“…As people ages, the ability of host defense mechanism may decrease with increase in the influence of accumulated periodontal destruction resulting in gradual tooth loss. Another epidemiologic study also suggested that specific bacteria played an important role in older adults with periodontal disease 26. In both univariate and multivariate logistic regression analysis of this study, old age groups showed significantly higher odds ratios and higher tooth loss rate.…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, the administration of metronidazole did not enhance the effects of SRP on A. actinomycetemcomitans in this group and the levels of this species did not differ at 6 months compared with baseline. Metronidazole has been proven effective against anaerobic periodontal pathogens in several studies (Loesche et al 1984, 1991, Feres et al 2001, Sigusch et al 2001) but its effects on A. actinomycetemcomitans are somewhat controversial (Aitken et al 1992, Loesche et al 1992, Saxen & Asikainen 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Metronidazole has been the focus of research in many years due to its antimicrobial activity against gram‐positive and gram‐negative anaerobes (68, 108). It can suppress subgingival pathogens like spirochetes, motile rods, P. intermedia, and P. gingivalis , and is effective in various forms of periodontitis (2, 38, 89–91, 120, 162, 210). However, there have been reports of reappearance with time of pathogenic bacteria after systemic metronidazole therapy (53, 108).…”
Section: Antimicrobial Effects Of Systemic Antibiotic Therapymentioning
confidence: 99%